PEMIKIRAN EKONOMI ISLAM ABAD VIII/14M - Suhartini; Ali Samsuri (Al-Iqtishad: Jurnal Ekonomi Syariah, 2024)
Islamic economics as an economy is based on the Islamic legal principles of the Koran and Al- Hadith. This situation makes Islamic economics have its own character in terms of definitions, principles, systems, rules and practices. Islamic economists who defined and explored the scope of Islamic economics included Imam Al-Syatibi and Ibnu Khaldun. Al-Syatibi has his own thoughts regarding Islamic economics, according to him, Islamic economics contains Maqashid sharia which consists of Dharuriyat, Hajjiyat, and Tahsiniyat. Apart from that, Al-Syatibi also has his own concept regarding objects of ownership and taxes. Ibnu Khaldun was one of the great Islamic scholars who lived during the dark ages of Islam or the beginning of the Renaissance period in Europe. His thoughts in the context of Islamic economics can be found in his monumental work "Muqadimmah" which provides many descriptions of the concept of national wealth, wage theory, international trade, taxes and market mechanisms and others which are very useful for the study and development of Islamic economics. Ibn Khaldun also succeeded in continuing Islamic economic thought which had become a tradition of Islamic intellectual thought from the prophetic era to the darkness of Islam.